Canada and the First World War : essays in honour of Robert Craig Brown - MacKenzie, David; Brown, Robert Craig (University of Toronto Press, 2018)
"The First World War is often credited as being the event that gave Canada its own identity, distinct from that of Britain, France, and the United States. Less often noted, however, is that it was also the cause of a great deal of friction within Canadian society. The fifteen essays contained in Canada and the First World War examine how Canadians experienced the war and how their experiences were shaped by region, politics, gender, class, and nationalism. Editor David MacKenzie has brought together some of the leading voices in Canadian history to take an in-depth look into the tensions and fractures the war caused, and to address the way some attitudes about the country were changed, while others remained the same. The essays vary in scope, but are strongly unified so as to create a collection that treats its subject in a complete and comprehensive manner. Canada and the First World War is a tribute to esteemed University of Toronto historian Robert Craig Brown, one of Canada's greatest authorities on the Great War World War One. The collection is a significant contribution to the on-going re-examination of Canada's experiences in war, and a must-read for students of Canadian history."-- Provided by publisher
Keywords: World War, 1914-1918 -- Canada.; Guerre mondiale, 1914-1918 -- Canada.; HISTORY -- Europe -- Western.; Canada; 1914-1918; Armistice Day.; Canadian.; Festschrift.; First World War.; The Great War.; WW1.; WWI.; armistice.; army.; history.; national transformation.; world war 1.; Electronic books.; Festschriften; Festschriften.